Gambaran Upaya Pencarian Pengobatan Diare di Wilayah Kerja Puskesmas yang Mendapat Nusantara Sehat berbasis Tim Batch I dan II - Aris Yulianto; Ida Diana Sari; Rini Sasanti Handayani (Jurnal Penelitian dan Pengembangan Pelayanan Kesehatan, 2020)
Diarrhea still becomes major public health problem, especially in remote and underdeveloped areas, borderland and outlying islands (DTPK) where most Nusantara Sehat health workers have been distributed to each primary healthcare center. The aim of this research is to investigate the habit of community seeks diarrhea medication pattern in the working area of primary healthcare centers where Team-based Nusantara Sehat health workers Batch I and II placed. The research was a descriptive cross sectional study and involved 12,381 families in 27 districts, 15 provinces, interventional and control primary healthcare centers, 30 each. Result showed that the prevalence of diarrhea cases based on diagnosis and recognition of respondents which had experienced liquid defecation 3 or more times a day were 1.9% and 0.6%, respectively. Oral rehydration salts (ORS) is the most dominant for diarrhea medication (31.1%). When seeking medication, 19.3% of respondents treated self-medication and 19.1% utilized health facility. This research concludes that there is still low self-medication care in treating diarrhea so that it needs to optimization using medicinal plants for the community with limited access to healthcare facilities.